DETERMINING BEST GRADUATES OBJECTIVELY USING THE WEIGHTED PRODUCT METHOD - Amalia Amalia (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2021)
Abstract: The purpose of education and teaching activities in higher education is to produce quality and effective graduates. Among the graduates there are of the best graduates for each study program each year. This study aims to find the best graduates who are able to compete in the world of work in accordance with stakeholder needs. The data processed in this study were sourced from the 2018 Royal Computer Information Management College graduates. The method used in this study is the Weighted Product method. The results of this study can determine the best graduates quickly and accurately. research can help in terms of decision makers for determining the best graduates in each college.             Keywords: Best Graduate; Student; Weighted Product  Abstrak: Tujuan kegiatan pendidikan dan pengajaran di perguruan tinggi adalah untuk menghasilkan lulusan yang berkualitas dan efektif. Di antara lulusan ada beberapa lulusan terbaik untuk setiap program studi tiap tahun. Penelitian ini bertujuan mencari lulusan terbaik yang mampu bersaing di dunia kerja sesuai dengan kebutuhan stakeholder. Data yang diolah dalam penelitian ini bersumber dari data lulusan Sekolah Tinggi Manajemen Informatika Komputer Royal tahun 2018 sebanyak 100 lulusan. Metode yang dipakai dipenelitian ini, metode Weighted Product. Hasil dari penelitian ini dapat menentukan lulusan terbaik secara cepat dan tepat. Penelitian dapat membantu dalam hal pengambil keputusan untuk penentuan lulusan terbaik disetiap perguruan tinggi.  Kata kunci: Lulusan Terbaik; mahasiswa;Weighted Product